Upscaling dan Diversifikasi Nilai Tambah Produk Unggulan Kelompok Wanita Tani Tunas Mulia - Nurdiani, Ulfah; Harahap, Fitri Amalinda; Maksum, Ali; Saputro, Wahyu Adhi (Penerbit Widina, Widina Media Utama, 2025)
Empowering women's farmer groups (KWT) is crucial for community development. One such growing KWT is the Tunas Mulia Women's Group (KWT) in Tambaksogra Village, Sumbang District, Banyumas Regency, which has a melon and pakcoy (vegetable) cultivation program. The availability of melons and pakcoy at KWT Tunas Mulia is quite high at certain times, resulting in low prices and some unsold surpluses. KWT Tunas Mulia still lacks understanding of product processing. This community service activity aims to upscale and diversify the added value of KWT Tunas Mulia's products. The community service method uses service learning, starting with education and counseling and ending with practical processing of melon products into ice cream and pakcoy into vegetable chips. The partners in this community service activity are all 15 members of KWT Tunas Mulia. This community service activity was carried out in August 2025. Based on the results of the community service activity, there was a transfer of knowledge understanding regarding the importance of product processing by KWT Tunas Mulia as well as the success of direct practice in processing melon and pakcoy harvested by KWT Tunas Mulia into ice cream and pakcoy vegetable chips optimally. The results of the evaluation questionnaire that measured the success of this community service had a percentage of 80%, so it can be concluded that this community service program is running well.ABSTRAKPemberdayaan kelompok wanita tani (KWT) penting dilakukan dalam rangka pembangunan masyarakat. Salah satu KWT yang sedang berkembang adalah KWT Tunas Mulia yang ada di Desa Tambaksogra, Kecamatan Sumbang, Kabupaten Banyumas yang memiliki program budidaya melon dan sayuran berupa pakcoy. Periode ketersediaan melon dan pakcoy di KWT Tunas Mulia pada waktu tertentu cukup banyak sehingga menyebabkan harga menjadi murah dan beberapa sisa tidak laku. Pemahaman pengolahan produk masih belum dilakukan oleh KWT Tunas Mulia. Kegiatan pengabdian ini bertujuan untuk upscaling dan diversifikasi nilai tambah produk dari KWT Tunas Mulia. Metode kegiatan pengabdian ini dengan service learning dimulai dengan edukasi dan penyuluhan dan diakhiri dengan praktik pengolahan produk melon menjadi es krim dan pakcoy menjadi keripik sayur. Mitra kegiatan pengabdian ini adalah seluruh anggota KWT Tunas Mulia sebanyak 15 orang. Kegiatan pengabdian ini dilakukan pada Bulan Agustus 2025. Berdasarkan hasil kegiatan pengabdian terjadi transfer knowledge pemahaman mengenai pentingnya pengolahan produk oleh KWT Tunas Mulia serta keberhasilan praktik langsung dalam mengolah melon dan pakcoy hasil panen KWT Tunas Mulia menjadi es krim dan keripik sayur pakcoy secara optimal. Hasil kuesioner evaluasi yang mengukur keberhasilan pengabdian ini memiliki persentase sebesar 80% dengan begitu dapat disimpulkan bahwa program kegiatan pengabdian ini berjalan dengan baik.